Korelasi Golongan Darah dan Kadar Hemoglobin pada Ibu Hamil - Kwarta, Cityta Putri; Ummah, Kholifatul; Imeldawati, Rakhmalia; Fathiyyah, Nurul; Ganisia, Ainun; Rochmayanti, Shinta Nur; Susila, Ida (Lontara Journal of Health Science and Technology, 2025)
Anaemia occuring during pregnancy represents a significant public health issue, especially in developing countries. Multiple sources have indicated a correlation between blood type and haemoglobin levels, but local data remains limited. This study aims to assess the distribution of ABO and Rhesus blood types and haemoglobin levels in pregnant women in rural Lamongan, Indonesia, and to evaluate the relationship between them. A cross-sectional study was conducted on 60 pregnant women at Ida Susila's Private Practice (November 2024–May 2025). Blood type data were obtained from the KIA Book, while haemoglobin levels were measured using a digital haemoglobin meter. For the data analysisi, the chi-square test and Spearman’s rho were the chosen statistical tools. Blood type O was the most common (46.7%), followed by B (25%), A (20%), and AB (8.3%). Most respondents were Rhesus positive (96.7%). The highest average haemoglobin levels were found in blood type AB (11.6 g/dl) and the lowest in blood type B (9.9 g/dl). Anaemia was most commonly found in blood group B. Blood group was found to be significantly associated with haemoglobin levels (p=0.009). Blood group, particularly, showed a higher tendency towards anaemia in pregnant women. Early screening of blood group and haemoglobin levels is important for promotive and preventive efforts against pregnancy-related especially in rural areas.